Impact of Social Media on Students' Academic Performance at Green Hope University, Garowe, Somalia - Shire, Abdinur Abdullahi (International Journal of Scientific Research and Management (IJSRM), 2024)
This study investigates how students at Green Hope University in Garowe, Somalia, perform academically in relation to social media, particularly Facebook and TikTok. In light of social media's pervasiveness in daily life, the study aims to determine how these platforms affect academic performance in this particular sociocultural context. Through surveys and questionnaires, information was gathered from 144 participants including students, instructors, parents, and university administration using a mixed-methods approach.The results showed that Facebook (r=0.480) and TikTok (r=0.550) had favorable relationships with academic achievement, indicating that social media can improve academic engagement when utilized carefully.But the study also emphasizes the necessity for students to utilize social media under supervision because excessive use can lead to distraction. Future research prospects are highlighted along with the ramifications for parents and educators.